KAJIAN TATA KELOLA IT BERDASARKAN INDEKS KAMI PADA UNIVERSITAS PAKUAN BOGOR - Nur Hidayati (LPPM Universitas Bina Sarana Informatika, 2014)
Corporate governance of information technology is becoming a very important needs for the sake of the survival of an organization. IT governance practices at the University of Pakuan (UNPAK) Faculty of MIPA Bogor in particular has not been done optimally , which still require evaluation in it, this was to be one of the goals in this study. By using descriptive types of qualitative research and exploratory that expected to know the condition of IT governance is ongoing. Results of the evaluation of the implementation of the IT governance is made by using index.KAMI Methode which is an adoption of ISO/IEC 27001, which is a tool to analyze the readiness of the security level of information about an organization's security framework. The maturity of the implementation of the corporate governance of information technology within the Faculty of MIPA UNPAK in level two, which is still in the process of the effectiveness and consistency of application framework used. Keywords : Index KAMI, Maturity, Information Technolgy